An investigation of the dielectric energy storage performance of Bi(Mg2/3Nb1/3)O3-modifed BaTiO3 Pb-free bulk ceramics with improved temperature/frequency stability. Issue 15 (15th October 2019) - Liu, Gang; Li, Yang; Shi, Mengqi; Yu, Linjiang; Chen, Peng; Yu, Kun; Yan, Yan; Jin, Li; Wang, Dawei; Gao, Jinghui
Abstract: In order to fabricate high performance dielectric capacitors for pulsed power applications, dense and homogenous Bi(Mg2/3 Nb1/3 )O3 -modifed BaTiO3 -based Pb-free relaxor ferroelectric ceramics were obtained through a isostatic pressing technique at room temperature. Obvious relaxor behavior with a high diffusion degree is confirmed by broad and frequency-dependent dielectric peaks in 0.875BaTiO3 -0.125Bi(Mg2/3 Nb1/3 )O3 (BT-0.125BMN). Good energy storage properties including a high recoverable energy density of ∼1.89 J/cm 3, an relatively high efficiency of ∼83%, good dielectric/temperature/frequency dependent stability and also fatigue resistance are achieved in this composition at a high electric field of 240 kV/cm, together with a fast discharging speed of <160 nm and high maximum current density of 503.46 A/cm 2 and a large power density of 25.12 MW/cm 3 . These properties indicate that BT-0.125BMN is a promising candidate of capacitors for the pulsed power applications.